Skin cells as a tool in genetic diagnosis of Duchenne muscular dystrophy - Tyers, Lynn (Division of Human Genetics, 2017)
Duchenne muscular dystrophy (DMD) is the most common and severe of the dystrophies, with an incidence of 1 in 3500 live male births, worldwide. Becker Muscular dystrophy (BMD) has a lower incidence of approximately 1 in 17500 births, a milder progression and longer life expectancy. Many advancements have been made in the development of gene-based therapies for the treatment of D/BMD, however, these treatments require genetic confirmation of the disease which continues to present a significant diagnostic challenge. The current standard for RNA-based analysis requires obtaining an invasive, often distressing, muscle biopsy. This dissertation investigated the utility of human autologous epidermal melanocyte and dermal fibroblast cell cultures for use as a tool for genetic confirmation of D/BMD from a much less invasive shave skin biopsy. Methodologies included immunohistochemical, immunocytochemical, Western blot, qPCR analysis and cDNA sequencing. The results suggest that melanocytes and fibroblasts express the full length muscle isoform of dystrophin, although at differing levels, and that melanocytes could potentially be used as an alternative for the genetic confirmation of D/BMD.